ANALISIS DEBIT AIR DAN AIRTANAH DANGKAL DAERAH ALIRAN SUNGAI (DAS) PRUMPUNG, KABUPATEN TUBAN - Riyan Niagara; Yanuar Purwanto; Yuli Suharnoto (Graduate School Bogor Agricultural University (SPs IPB), 2016)
The water demand increases in line with the growths of population, industry and business, but the water availability is ascertained to satisfy those needs continuously. Therefore, it is necessary to analyze water availability in a specified watershed integrated with various aspects in hydrology. The objective of this study were (1) to identify of landuse at Prumpung watershed,(2) to determine water availability in Prumpung watershed by analyzing the relationship of rainfall and river discharge using the Soil and Water Assessment Tool (SWAT) and (3) to influence government policies relation with urban planning of Tuban Regency. The watershed is located in Tuban Regency and based on urban planning of Tuban Regency 2012-2032 which is covering 22,319.14 ha. Input data were Digital Elevation Models, land use, and soil map. The procedures were including collection and process of climate data, trend analysis of water availability, discharge measurements, discharge analyze and calibration using SWAT. The results of existing landuse showed that the minimum water discharge was 0.338 m3/s to the maximum 5,945 m3/s with groundwater availability was maximum until 3,070 mm on July to September 2014. SWAT has generated 27 HRUs that described the spatial condition of the whole watershed. Calculated discharges with SWAT compared to the measured discharges having The NashSutcliffe Efficiency (NSE) of 0.77 and correlation coefficient of 0.79. Conservation scenario has been conducted at several landuses for water availability and based on conservation area. The results showed that the minimum water discharge was 0.334m3/s to the maximum 4.842 m3/s with groundwater availability was maximum until 3,140 mm. There were no significant change of groundwater based on urban planning and scenario at Prumpung watershed, Tuban Regency.Identification of Prumpung watershed produced relatively small water discharge compared than water demand based urban planning of Tuban Regency. A plan of water management for exploiting of high rain fall in rainy season will contribute in consideration of the appropriate water supply/demand balance in dry season.